Phase III trials - Edelman, Martin (Henry Stewart Talks, 2009)
Phase III trials: definition and difficulties, Statistical aspects: planning, execution and analysis, Why phase III trials?, Phase II results are not always correct, Unsuspected risks and benefits may be revealed, Economic analysis, The future of phase III trials, Targeted therapies and targeted populations, How to use phase III results
Archived at 2021/02/25